Letter : Grant - International Solidarity Fund - Prain, Robert
034-0132-001 Light and Liberty. Electrical Trades Union. EXECUTIVE COUNCIL. Telephone: MACAULAY 2223-4 All Communications to be addressed to: J. ROWAN. J.P., General Secretary. IMPORTANT. Please deal with one subject only. Telegrams: "ELTRADION, CLAPCOM, LONDON." General Office: 11 MACAULAY ROAD, CLAPHAM COMMON, LONDON, S.W.4. Please Quote in Reply. Your Ref Our Ref RP/HH. SUBJECT: Grant - International Solidarity Fund. Sept., 1938. Sir Walter Citrine, General Secretary, Trades Union Congress, Transport House, Smith Square, LONDON, S.W.1. Dear Sir, At a meeting of our Executive Council held on 10th September the question of granting some assistance to the International Brigade Dependants and Wounded Aid Committee, was considered. Your letter dated 30th August on this subject was also before our Executive Council. In addition it was reported by members who had attended the T.U.C., that grants to the International Solidarity Fund could be earmarked for the International Brigade Dependants and Wounded Aid Committee. It was eventually decided to make a grant of £100 to the International Solidarity Fund and this amount be earmarked for the International Brigade Dependants and Wounded Aid Committee. I herewith enclose cheque for £100, and no doubt you will make the necessary arrangements to have the money transferred as suggested. Yours faithfully, for the ELECTRICAL TRADES UNION. Robert Prain Asst. General Secretary. ENCL: Cheque £100. 292/946/34/132